The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1468-1331.2009.02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Total daily sleep duration and the risk of dementia: a prospective population‐based study

Abstract: Prolonged sleep duration (night-time sleep and daytime napping) may be associated with an increased risk of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
4
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(145 citation statements)
references
References 29 publications
10
127
4
4
Order By: Relevance
“…p for quadratic regression 00.179; <4-7.9 h: p for trend 00.500; 7-≥10 h: p for trend00.006 has been adjusted for age, gender, years of education, smoking habit, regular alcohol, tea and coffee consumption, insomnia, depression (GDS≧8), psychotropic medications, diabetes mellitus, hypertension, stroke, chronic obstructive pulmonary disease, coronary heart disease, and habitual snoring. Our observations were consistent with the work of others who have revealed that cognitive deficit was associated with longer sleep duration (Faubel et al 2009;Benito-Leon et al 2009;Schmutte et al 2007). It is uncertain whether it is the co-existing morbidities, for which we have adjusted as far as possible, or the poor sleep quality associated with cognitive decline that prolonged sleep duration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…p for quadratic regression 00.179; <4-7.9 h: p for trend 00.500; 7-≥10 h: p for trend00.006 has been adjusted for age, gender, years of education, smoking habit, regular alcohol, tea and coffee consumption, insomnia, depression (GDS≧8), psychotropic medications, diabetes mellitus, hypertension, stroke, chronic obstructive pulmonary disease, coronary heart disease, and habitual snoring. Our observations were consistent with the work of others who have revealed that cognitive deficit was associated with longer sleep duration (Faubel et al 2009;Benito-Leon et al 2009;Schmutte et al 2007). It is uncertain whether it is the co-existing morbidities, for which we have adjusted as far as possible, or the poor sleep quality associated with cognitive decline that prolonged sleep duration.…”
Section: Discussionsupporting
confidence: 91%
“…Some reported poor cognition in older persons sleeping for longer duration (Faubel et al 2009;Benito-Leon et al 2009;Schmutte et al 2007) while others demonstrated the opposite (Ohayon and Vecchierini 2005;Tworoger et al 2006). Kronholm et al (2009), furthermore, has revealed an inverted U-shaped relationship between sleep duration and cognitive function in the general population, while Xu et al (2011) have recently reported a similar relationship in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…37-MMSE) were associated with potential confounding variables. The 37-MMSE was correlated with age (r S = −0.297, p < 0.001), gender (mean ± SD [median] = 31.3 ± 5.5 [33] in men vs. 29.5 ± 4.8 [30] in women, Mann-Whitney U test, p = 0.001), educational category (r S = 0.33, p < 0.001), subjective depressive symptoms (28.3 ± 4.9 [29] in those who responded "yes" vs. 30.7 ± 5.1 [32] in those who responded "no", Mann-Whitney U test, p < 0.001). The 37-MMSE was marginally correlated with medications that could affect cognition (mean ± SD [median] = 29.4 ± 5.3 [30] in those taking a medication vs. 30.4 ± 5.0 [31] in those who do not take a medication, Mann-Whitney U test, p = 0.12).…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, the 37-MMSE was adopted to Chilean, Maltese, and Spanish socio-cultural backgrounds and then validated against clinical diagnoses of dementia [21,22,[30][31][32][33]. The 37-MMSE included all of the standard MMSE [30] items as well as three additional items: 1) an attention task, i.e., say 1, 3, 5, 7, 9 backwards; 2) a visual order, i.e., a man raising his arms; and 3) a simple construction task, i.e., copying two overlapping circles [21,22,[30][31][32][33].…”
Section: Neuropsychological Batterymentioning
confidence: 99%
“…In addition, dementia, sleep complaints, and sleep-related problems are known to increase with age (Wolkove et al 2007a, b;Bastos Leite et al 2004;Plassman et al 2007;Wu and Swaab 2007). Although there is sufficient evidence from humans and experimental animals on the association between sleep disorders and dementia, these topics have not yet been explored in the very elderly population (Rose et al 2010;Riegel and Weaver 2009;Yu et al 2009;Haimov et al 2008;Benito-León et al 2009;Hasan et al 2012). Therefore, it is important to clarify the association between sleep disorders and dementia in this age group.…”
Section: Introductionmentioning
confidence: 99%